Etika Bisnis Islam Pedagang Kaki Lima Pada Taman Bersemi STQ Sangatta - Eko Nursalim; Elga Putri Asri; Mucrifah; Cindy Tri Kusuma Alam; Zahrotun Ni'mah (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
The purpose of this research is to find out how the business behavior of street vendors in Taman Bersemi STQ Sangatta, the factors that influence the application of Islamic business ethics and the business behavior of street vendors in Taman Bersemi STQ Sangatta is in accordance with Islamic business ethics. The type of research that the author uses in this study is descriptive field research using a qualitative research approach. The informants in this study were street vendors in STQ Sangatta Bersemi Park and managers, namely BUMDes Sangatta Utara Sejahtera. Data collection using observation, interview and documentation methods, are then collected and processed descriptively qualitative. The results of the study concluded that the business behavior of street vendors in Taman Bersemi STQ Sangatta did not know Islamic business ethics. However, the traders run a trading business or buy and sell using the rules that have been regulated by Islam, especially honesty, Factors that influence the application of Islamic business ethics of street vendors in Taman Bersemi STQ Sangatta, namely: honesty, selling halal goods, selling goods of good quality, not hiding defects in goods, not committing perjury, generous, not competing with other traders, keeping promises, issuing zakat when it reaches the nisab, not neglecting to carry out Allah's commands, The business behavior of street vendors in Taman Bersemi STQ Sangatta is in accordance with the principles of Islamic business ethics, namely unity (tawhid), balance (justice/Equilibrium), free will (ikhtiar/free will), responsibility (responsibility), policy (ihsan). Keywords: Islamic business ethics, STQ Sangatta, Street vendors